Matters of Multiplication: - Smithrosser, Elizabeth; Hardie, Alison; Bizais-Lillig, Marie; De Giorgi, Laura; Klotzbücher, Sascha; Kraushaar, Frank; Schweiger, Irmy (Journal of the European Association for Chinese Studies, 2025)
The editorial committee is pleased to present volume 6.1 of the Journal of the European Association for Chinese Studies, which opens with a special section on “Ciphering and Ruling Modern China’s Population”. 編委會榮幸地推出《歐洲漢學學會學刊》第六卷第一期。本期特設“近代中國人口的編碼與治理”專題，作為開篇內容。